ANTIHYPERTENSIVE DRUG THERAPY IN NEPAL: FINDINGS FROM MAY MEASUREMENT MONTHS 2019. (April 2021) - Neupane, Dinesh; Dhungana, Raja Ram; Bhattarai, Harikrishna; Adhikari, Tara Ballav; Koirala, Sweta; Khanal, Pratik; Khatiwoda, Shiva Ram; Kallestrup, Per; Koirala, Bhagawan; Matsushita, Kunihiro; Olsen, Michael Hecht; Poulter, Neil; et al.
Abstract : Objective: To explore the pattern of the antihypertensive medication use among Nepali patients. Figure. No caption available. Design and method: This cross-sectional study in Nepal analysed data from the May Measurement Month 2019 (MMM19). We converted all trade names to generic names and further categorized according to class of medication. Participants who provided the information about the name of their antihypertensive medication at the time of interview were included. Blood pressure (BP) control was defined as a systolic BP < 140 mmHg and diastolic BP < 90. Results: Out of 72, 320 who participated in the MMM19, three BP readings were available for 66, 955 (93%). Among them, 15, 872 (24%) had hypertension and 7, 507 (47%) were taking antihypertensive medication. Out of them, 1, 434 (19%) provided the information about the antihypertensive medication. The mean (SD) of systolic and diastolic blood pressure were 135 mmHg (17 mmHg) and 86 mmHg (11 mmHg). Among those treated for BP, 85%, 14% and 1% used 1, 2 and > 2 drugs respectively and 63% were controlled. The proportion of patient taking calcium channel blockers (CCB), angiotensin II receptor blockers (ARBs), and CCB plus ARB were 56%, 24% and 10%, respectively. Amlodipine was the most widely used medicine (55 %) followed by losartan (15%). Blood pressure control rate among participants using telmisartan, losartan plus hydrochlorothiazide, amlodipine plus losartan, losartan and amlodipine were 75%, 68%, 64%, 62% and 62%, respectively. Conclusions: Among individuals taking antihypertensive medications in Nepal, 85% of patients were taking monotherapy, mostly amlodipine. Improvements in BP control will likely require intensification of therapy, potentially through greater use of fixed dose combination therapy.